FEATURES CHARACTERISTIC OF THE UZBEK PEOPLE IN THE WORKS OF TOGAI MURAD (International journal of artificial intelligence, 2025)
in the literature of Uzbekistan there are many writers who reflect the traditions and way of life of the values of the Uzbek people. One of them was the uncle Murad, whose works covered not only Uzbek literature, but also world literature. In his unique Sitili, togai Murod illuminates the contemporary worldviews and values of the Uzbek people through his social and pischological threats. A special place in his works is occupied by the devotion of our people to love, family values, national traditions and the spirit of the wrestler.